ANALYSIS OF NEEDS AND CONSTRAINTS IN THE FARMER GROUP EMPOWERMENT PROGRAM IN THE USE OF ORGANIC FERTILIZERS IN KALISAT DISTRICT, JEMBER REGENCY - Argarisma, Feni; Kustiari, Tanti; Muksin, Muksin (ITScience (Information Technology and Science), 2023)
Procurement of organic fertilizers is one of the efforts that can be made to restore soil organic matter to increase the production value of the agricultural sector in Jember Regency. Issues about the environment and low soil organic nutrient content also occur in Jember District, especially in Kalisat District, which causes the importance of applying organic fertilizers. The importance of using organic fertilizers requires the participation of farmer groups to be more empowered in producing and using organic fertilizers. The purpose of this study was to analyze the needs and constraints faced to develop a strategy for developing a farmer group empowerment program in the use of organic fertilizers in the Kalisat subdistrict, regency Jember. This research is classified as a qualitative research which aims to analyze the key factors in the farmer group empowerment program. The results showed that in the elements of program needs there were two needs which were key factors, namely organic farming production facilities and local government policies. In the element of constraint there are two key obstacles namely the low knowledge of farmers and the limitations of organic fertilizer processing tools and machines. The resulting strategy is in the form of: 1) Addition of organic farming production facilities. 2) Alignment of local government policies by adding programs to promote the use of organic fertilizers in Jember Regency in the main program of Jember Mandiri. 3) Increase farmer's knowledge related to the manufacture of organic fertilizers through counseling.